Utilization of Preconception Care and Its Associated Factors among Pregnant Women of West Guji Zone, Oromia, Ethiopia, 2021: A Community-Based Cross-Sectional Study - Elias Amaje; Anteneh Fikrie; Takala Utura (SAGE Publishing, 2022)
Background Regardless of its benefit in promoting maternal health, contributing to a healthy pregnancy, little is known concerning the prevalence of utilization of preconception care and its determinant in southern Ethiopia. Hence, this study designed to determine the prevalence of utilization of preconception care and contributing factors among pregnant women in West Guji Zone, Southern Ethiopia, 2021. Methods A community-based cross-sectional study was conducted among systematically selected 660 pregnant women in West Guji from June 15 to July 30, 2021. A pretested interviewer-administered structured questionnaire was used to collect the data. Data entry was done in Epidata version3.1 and exported to SPSS version 25 for analysis. Descriptive statistics were used to summarize the data. To identify the factors associated with the utilization of preconception care binary and multivariable logistic regression analysis was performed. Adjusted odds ratios (AOR) with 95% CI were estimated to assess the strength of associations and statistical significance was declared at a p-value < 0.05. Results One hundred-forty seven, 22.3% [95% CI (19.2, 25.4)] of mothers utilized preconception care. Being college and above [(AOR = 5.51 95%CI 91.43-21.19)] and secondary [(AOR = 4.46 95%CI (1.38-14.39)] in educational status, rich [(AOR = 4.23 95%CI (1.32-13.55)], having good knowledge about preconception care [AOR = 2.34 95%CI (1.05-5.28)], having a positive attitude towards preconception care [(AOR = 9.99 95%CI (4.25-23.48)] and deciding with her husband regarding maternal health services [(AOR = 4.71 95%CI (1.91-11.56)] were factors positively affecting utilization of preconception care. Conclusions The utilization of preconception care in the study area is low. Being college and above and secondary in educational status, rich, good knowledge, positive attitude towards preconception care, and deciding with her husband regarding maternal health services were independent factors promoting the utilization of preconception care. Information, education, and communication activities should be strengthened to increase awareness of mothers about preconception care.